Using mobile devices in a high risk context: The role of risk and trust in an exploratory study in Afghanistan. (May 2015) - Marett, Kent; Pearson, Allison W.; Pearson, Rodney A.; Bergiel, Erich
Abstract: Mobile phone adoption and use are common-place in the western world, yet still are associated with risks of loss of privacy and information security. However, in high-risk cultures and countries, such as those at war or threatened by terrorism, mobile phone adoption and benefits of use may be perceived quite differently. In this study, we use e-commerce and adoption theories to build a model of trust and risk as predictors of mobile use benefits in a sample of current mobile users in southern Afghanistan. The responses collected from a survey of over seven thousand Afghani citizens were used to test the research model. The results suggest that despite the potential danger, the mobile device owners who were surveyed perceived the benefits derived from use as being worthwhile. The results are discussed with implications for managers and practitioners provided. Highlights: We examine the adoption and use of mobile devices in war-torn Afghanistan. Data was collected from over three thousand Afghani mobile device users. Afghani mobile users reported moderate levels of distrust in their mobile service providers. The desire for information and connectivity seems to outweigh the perceived risks of use.